2021
DOI: 10.1016/j.yebeh.2021.107922
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive study of patients diagnosed with psychogenic nonepileptic seizures at a tertiary epilepsy center in the Czech Republic: One-year follow-up

Abstract: To delineate sociodemographic data of a large sample of Czech Republic patients diagnosed with psychogenic non-epileptic seizures (PNES) at the time of diagnosis and at a follow-up visit one year after discharge.This study collected reports of past stressors, quality of relationships in childhood, family background, traumatic events, and recent adversities in patients diagnosed with PNES. Method: Patients (219w/79m, 37.56 (13.15) years, 12.13 (2.05) years of education) were assessed through a semi-structured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…Furthermore, an outcome study revealed that even after being correctly diagnosed, of those who continued to experience seizures, nearly 30% became unemployed [4,5] and over half applied for disability status/social security benefits [4,6]. Similarly, a descriptive study of PNES patients seen in a tertiary epilepsy center in Czech Republic found that nearly 50% of the sample was receiving disability benefits [7]. Another study that included various FNDs found that patients who reported greater distress were more likely to be unemployed citing health reasons and were more likely to be receiving disability-related assistance when compared to patients with symptoms explained by a neurological disease [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an outcome study revealed that even after being correctly diagnosed, of those who continued to experience seizures, nearly 30% became unemployed [4,5] and over half applied for disability status/social security benefits [4,6]. Similarly, a descriptive study of PNES patients seen in a tertiary epilepsy center in Czech Republic found that nearly 50% of the sample was receiving disability benefits [7]. Another study that included various FNDs found that patients who reported greater distress were more likely to be unemployed citing health reasons and were more likely to be receiving disability-related assistance when compared to patients with symptoms explained by a neurological disease [8].…”
Section: Introductionmentioning
confidence: 99%